UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX MTsN 3 ACEH BARAT MELALUI METODE INKUIRI - Misnelly Misnelly (Universitas Islam Sumatera Utara, 2020)
This study aims to determine the increase in activity and student learning outcomes as well as what efforts need to be made to increase student activity and learning outcomes on the subject of Statistics through learning the inquiry method. The subjects in this study were 30 students of class IX-D MTsN 3 Aceh Barat. This study consisted of 2 cycles. After being given action through the inquiry method and using LAS in cycle I, it was found that the active student average was 20%. From the second cycle, it was found that the active student average was 76.66%. Based on the criteria for learning activities, this learning has achieved the target of increasing learning activities. Before giving action, students are given a preliminary test, and at the end of each cycle, a learning outcome test is given. The number of students who achieved mastery learning from the initial test was 13.33% with a class average of 44.0. The results of data analysis in the first cycle after learning through the inquiry method, many students who achieved learning completeness were 66.67% with a class average of 68.67. These results have increased at the end of cycle II with the same learning strategy, many students who achieved learning completeness were 90%, and the class average was 72.67. Based on the criteria of classical learning completeness, this learning has achieved the target of classical learning completeness.